In vitro proportional investigation of different Pantoprazole sodium brands of gastro-resistant tablets - Hindustan Abdul Ahad; Chinthaginjala Haranath; Rahul Raghav Dasari; Madana Gowthami; Naga Jyothi Varam; Pandyala Sravanthi (Kuwait Journal of Science)
The present work was to a comparative exploration of some physicochemical possessions viz., weight change, thickness, diameter, hardness, disintegration time, in-vitro drug discharge and analyse studies of various commercially available Pantoprazole sodium tablets (PST) of 40 mg. The hardness, loss on friability, dissolution test, disintegration test and uniformity of drug content were evaluated. All the brands meet the requirements as per the pharmacopoeial standards. The dissolution profile study revealed that PST-1 had faster while PST-2 has slower. The dissolution informations were kinetically treated.